The Effects of Surprises Factors Macroeconomic to Earnings Surprises and Market Liquidity and Impact to Stock Return. - Noldy Takaliuang (Journal of International Conference Proceedings (JICP), 2019)
This paper approach a Structural Equation Model design by method Asymptotically Distribution Free (ADF) to analyzed the surprises factors macroeconomic affect the stock return with both market liquidity and earnings surprises. The monthly financial sector data with 59 firms’ for the years 2012-2016 and using the purposive sampling method. The result indicated that’s surprises factors macroeconomic is significant to earnings surprises and stock returns also earnings surprises to returns but not to market liquidity and liquidity to stock returns.